NORMA PEDAGOGIS DAN ANALISIS KEBUTUHAN BELAJAR DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK PENUTUR ASING (BIPA) - Suyitno, Imam (Diksi, 2015)
The teaching-learning process of Indonesian involving foreigners as the learners differs in characteristics from the teaching-learning process of Indonesian in general. The differences are due to the learners’ cultural backgrounds. An analysis of their learning needs and pedagogical norms of language learning is required in the selection of the materials and strategies for the teaching-learning process of Indonesian involving them as the learners. Results of analysis on their entry level, learning style, and learning objective will direct the teachers in selecting the language teaching materials and strategies. In addition, the materials and strategies are also influenced by the teachers’ own pedagogical norms. Keywords: needs analysis, pedagogical norms, teaching materials, teaching strategies